Organizational Communication Model of The Village Fund Governance (Case Study on Corruption of Village Funds in Dasok Village, East Java) - Rachmi Kurnia Siregar; Amin Aminudin (Nyimak: Journal of Communication, 2022)
This study aims to determine the organizational communication of the Dasok Village Head in East Java regarding the management of the Village Fund. This research method uses a case study with a qualitative approach. Data collection techniques were carried out through in-depth interviews, observations, and literature studies. The results showed that the Dasok Village Head violated the authority given by the state by not involving the Village Consultative Body (BPD) as a representation of the community, thus causing the Village Fund to be prone to corruption. The communication carried out by the Village Head takes place in a linear (one-way) manner. On that basis, the government should encourage village heads to build intensive communication and dialogue with the BPD and village communities. As a solution to minimize cases of corruption in the Village Fund, the application of local wisdom values and a cultural value system is a necessity that is carried out by the government so that the objectives of the Undang-Undang Desa No. 6 Tahun 2014 namely villages to become advanced, independent, democratic, and have prosperous citizens can be achieved.Keywords: Corruption, local wisdom, organizational communications, village fund ABSTRAKPenelitian ini bertujuan untuk mengetahui komunikasi organisasi Kepala Desa Dasok Jawa Timur terkait pengelolaan Dana Desa. Metode penelitian ini menggunakan studi kasus dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi dan studi pustaka. Hasil penelitian menunjukkan Kepala Desa Dasok menyalahi kewenangan yang diberikan negara dengan tidak melibatkan Badan Permusyawaratan Desa (BPD) sebagai representasi masyarakat, sehingga menyebabkan Dana Desa rawan korupsi. Komunikasi yang dilakukan Kepala Desa berlangsung secara linier (satu arah). Atas dasar itu, pemerintah harus lebih mendorong kepala desa untuk membangun komunikasi dan dialog intensif dengan BPD maupun masyarakat desa. Sebagai solusi menimalisasi kasus-kasus korupsi Dana Desa, penerapan nilai-nilai kearifan lokal dan sistem nilai budaya menjadi suatu keniscayaan yang dilakukan pemerintah agar tujuan Undang-Undang Desa No. 6 Tahun 2014 yakni desa menjadi maju, mandiri, demokratis, dan warganya sejahtera dapat tercapai.Kata Kunci: Dana desa, kearifan lokal, komunikasi organisasi, korupsi